High phenotypic variation of seed traits, germination characteristics and genetic diversity of an invasive annual weed. Issue 1 (10th January 2013) - Hantsch, Lydia; Bruelheide, Helge; Erfmeier, Alexandra
Abstract: Both phenotypic and genetic variation can affect the establishment success of exotic species. Using the weed Senecio vernalis Waldst. & Kit. with a continuous westward expansion of the native geographic range, we asked to what degree seed traits and germination patterns differ among different habitat disturbance types in the introduced region. We hypothesized that seed traits and germination pattern differ between different disturbance types, with lighter seeds and enhanced germination speed in highly disturbed habitats. Since S. vernalis colonizes successfully various disturbed habitats, we expected to find a high phenotypic genetic variation. Individuals from 19 populations were sampled from one region in Eastern Germany to study seed trait variation and germination success by means of a germination experiment and to assess genetic patterns using amplified fragment length polymorphism (AFLP) markers. Contrary to our expectation, habitat disturbance types did not differ in seed traits, germination characteristics or genetic variation. Instead, we found highest phenotypic and genetic variation within populations. Maximum percentage of germination was positively affected by seed mass. In addition, there was a weak but significant association between AFLP band patterns and population size and seed width, indicating that some variation in seed traits has a genetic component. In conclusion, the absence of a population differentiation at this geographic scale makes it unlikely that adaptation to different disturbance regimes is involved. Instead, a high variation in seed traits, overall high germination and genetic variation within populations under a wide range of habitat disturbance conditions seems to enable the offspring to colonize various habitat disturbance types.